Blue luminescent graphene quantum dots by photochemical stitching of small aromatic molecules: fluorescent nanoprobes in cellular imaging - Gokhale, Rohan; Singh, Pooja (Particle & Particle Systems Characterization, 2014)
Blue fluorescent graphene quantum dots (GQDs) are synthesized from small haloaromatic molecules by laser photochemistry. The process involves a bottom-up photochemical stitching mechanism of the free radicals generated by irradiation of ultraviolet photons (lambda = 248 nm) on o-dichlorobenzene. The GQDs are further demonstrated to be of importance as fluorescent nanoprobes in bioimaging of cells.image
Keywords: bioimaging; free radicals; graphene quantum dots; photochemical stitching; UV laser